Peran Guru PAI Sebagai Pembimbing Dalam Pembinaan Sopan Santun Peserta Didik di Madrasah Aliyah Sunan Ampel Pare Kediri - Dhuha Rohmawan (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2023)
The role of education, especially a teacher, is very necessary for forming and cultivating character in students. The teacher as a role model for his students in shaping provides examples of good character so that they can produce good generations as well. Responding to the problems that occur, the author conducts research with the title "The Role of PAI Teachers as Guides in Fostering Student Politeness at Madrasah Aliyah Sunan Ampel Pare Kediri ". This study aims to 1) Know the role of PAI teachers as guides in fostering student manners at Madrasah Aliyah Sunan Ampel Pare Kediri, 2) Know the methods applied by PAI teachers in fostering student manners at Madrasah Aliyah Sunan Ampel Pare Kediri and 3) Know the supporting factors and obstacles for PAI teachers in fostering student manners at Madrasah Aliyah Sunan Ampel Pare Kediri . This type of research uses qualitative (qualitative research) with a qualitative descriptive research method with a phenomenological approach, in the collection procedure, namely: observation, interviews and documentation. The data obtained were analyzed by means of data collection, data reduction, data presentation and drawing conclusions. Test the validity of the data using technique triangulation and source triangulation. As for the results of the study, it shows that 1) The role of the PAI teacher as a guide in fostering manners at Madrasah Aliyah Sunan Ampel Pare Kediri , namely: the teacher as a guide and the teacher as habituation. 2) The methods applied to support the development of manners in Madrasah Aliyah Sunan Ampel Pare Kediri are: the exemplary method (uswah) and the habituation method. 3) The supporting factors and inhibiting factors for the PAI teacher as a guide in fostering manners at Madrasah Aliyah Sunan Ampel Pare Kediri are: supporting factors, namely being within the scope of Islamic boarding schools and the existence of a strategic program from the madrasa and inhibiting factors, namely the lack of awareness in students.